Investigation of membrane condensation induced by CaCO3 nanoparticles and its effect on membrane protein function. Issue 79 (26th October 2017) - Luo, Ke; Jeong, Ki-Baek; Oh, Jae-Min; Choi, Soo-Jin; Jeon, Tae-Joon; Kim, Young-Rok
Abstract : Investigation of membrane condensation induced by calcium ions released from nano-CaCO3 . Abstract : The membrane dynamics both across the lipid bilayer and in the lateral lipid domains play an important role in a number of key cellular processes including the normal functions of membrane proteins. Herein, we report an electrical method to monitor the changes in membrane dynamics with respect to the interactions between the lipid bilayer and CaCO3 nanoparticles (nano CaCO3 ). Through transmembrane capacitance measurements, the electrostatic interaction between lipid molecules and Ca 2+ ions dissolved from nano CaCO3 turned out to be responsible for the membrane condensation, whereas nano CaCO3 itself didn't show any notable interaction with the lipid bilayer. Moreover, the activities of gramicidin represented by the channel forming rate and lifetime of the channel were shown to be greatly influenced by nano CaCO3 . These findings demonstrate that a potential cytotoxicity of nano CaCO3 could be derived from the dissolved Ca 2+ ions, but not from nano CaCO3 itself, affecting cellular membrane dynamics by lipid condensation.